2020
DOI: 10.1039/d0ra00520g
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of a deactivated surface functionalised polyacrylonitrile supported Fenton catalyst for use in wastewater treatment

Abstract: Successful attempts to regenerate a used surface functionalised nanocoated polyacrylonitrile (PAN) catalyst are described here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…The FTIR assignments of the ion exchange PANF can be found in Table 4 and as indicated in previous papers. 23,44 In short, the groups present on the ion exchange PAN consist of amidoximes (CN–OH) and hydrazines (C–NH–NH 2 ) Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR assignments of the ion exchange PANF can be found in Table 4 and as indicated in previous papers. 23,44 In short, the groups present on the ion exchange PAN consist of amidoximes (CN–OH) and hydrazines (C–NH–NH 2 ) Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, many studies are conrming that the catalyst deactivation was mainly occurred due to extended leaching of iron into the solution. 19 In another study, Lejin Xu and Jianlong Wang concluded that the causes of deactivation was mainly due to surface oxidation of Fe 2+ to Fe 3+ by generated OH radicals during the course of reaction. Therefore, preserving the catalytic activity and stability is continue to be a challenging towards the Fenton oxidation reaction.…”
Section: Introductionmentioning
confidence: 99%